2019
DOI: 10.1111/1471-0307.12642
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis and textural properties of low‐fat ultrafiltered Feta cheese as influenced by maltodextrin

Abstract: Maltodextrin was used as a fat replacer in low-fat ultrafiltered cheese. Fat was replaced with 25% maltodextrin milk solution (w/w) in cheese at 15 and 50% (w/w). The chemical, rheological and sensory properties as well as the microstructure of the cheese samples were evaluated after storage for 2 months at 8°C. Maltodextrin affected the chemical (pH, dry matter, fat, water-soluble nitrogen to total nitrogen, nonprotein nitrogen to total nitrogen, total free amino acid) and rheological (mean relaxation time) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…Cheese texture is influenced by the protein, fat, water contents, and biochemical activities. Casein is the main structural component of cheese that present in the form of a network in the cheese matrix (Nazari, Mortazavi, Hesari, & Tabatabaei Yazdi, 2019). There are a lot of dairy products, in which vegetable proteins can be used to obtain novel products and enrich milk as a solution to the problem of milk availability, nutritional problems, and production costs.…”
mentioning
confidence: 99%
“…Cheese texture is influenced by the protein, fat, water contents, and biochemical activities. Casein is the main structural component of cheese that present in the form of a network in the cheese matrix (Nazari, Mortazavi, Hesari, & Tabatabaei Yazdi, 2019). There are a lot of dairy products, in which vegetable proteins can be used to obtain novel products and enrich milk as a solution to the problem of milk availability, nutritional problems, and production costs.…”
mentioning
confidence: 99%
“…Several authors have linked limited proteolysis to the development of a harder texture [44,45]. The influence of breed on the texture of hard cheeses was described by several authors [46][47][48], although in this instance, significant differences were observed only in relation to adhesiveness or stickiness, and not to hardness.…”
Section: Sensory Analysis By Tasting Panelmentioning
confidence: 98%
“…En los últimos años, debido a las enfermedades asociadas con el aumento en el consumo de grasas, se han realizado muchos estudios sobre productos lácteos bajos en grasa incluido el queso como el queso Cheddar, mozzarella, el queso Feta, quesos en salmuera blanca filtrada (UF) y queso feta UF). (Nazari et al, 2020). Hay mucha evidencia que indica una relación entre un mayor consumo de grasas y un mayor riesgo de enfermedades como la obesidad, la aterosclerosis, la enfermedad coronaria, el daño del tejido canceroso y tipos de cánceres distintos.…”
Section: Fortificación En Quesosunclassified